2022
DOI: 10.1038/s41598-022-11528-7
|View full text |Cite
|
Sign up to set email alerts
|

Darcy resistance flow of Sutterby nanofluid with microorganisms with applications of nano-biofuel cells

Abstract: The objective of current research is to endorse the thermal aspect of Sutterby nanofluid containing the microorganisms due the stretched cylinder. The features of nonlinear thermal radiation, Darcy resistance and activation energy are also incorporated to inspect the thermal prospective. The problem is further extended with implementation of modified Fourier and Fick’s theories. The results are presented for the stretched cylinder and also for stationary plate. The numerical formulation for the problem is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1 . The governing equations signifying the flow under above norms are as follows 52 , 53 ; with
Figure 1 Coordinate system and flow diagram.
…”
Section: Problem Descriptionmentioning
confidence: 99%
“…1 . The governing equations signifying the flow under above norms are as follows 52 , 53 ; with
Figure 1 Coordinate system and flow diagram.
…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Aldabesh et al . 10 endorsed that the parametric effects change the nature of problems by considering Sutterby nano-fluid involving microorganisms over stretched cylinder. For showing these effects Darcy resistance, thermal radiation and activation energy play important role.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reduced that microorganisms’ significance decayed along with a larger growth in microbes’ concentration difference number, bio-convective Lewis and Peclet numbers. Aldabesh et al (2022) probed the Darcy resistive flow of nanofluid induced by the effects of microorganisms past an elongating cylinder and concluded that velocity distribution decays as the Darcy parameter increases. Madhukesh et al (2022) discussed the role of SWCNT nanoparticles subject to a combination of microorganisms past a Riga sheet and concluded that velocity distribution is reduced when thermal layers have augmented due to larger volume fractions.…”
Section: Introductionmentioning
confidence: 99%